On Relationship Between Ambiguity Function and Linear Canonical Ambiguity Function - Bahri, M. (Springer Science and Business Media Deutschland GmbH, 2022)
The linear canonical ambiguity function is a time frequency analysis method which combines the classical ambiguity function with the linear canonical transform. In the present work, we explore a direct relation between the linear canonical ambiguity function and the classical ambiguity function. We then utilize this interesting relation to obtain its fundamental properties such as the inversion theorem, general Moyalâs formula and conjugate function. Finally, the linear canonical ambiguity function method is applied to evaluate the linear FM signal. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.